Lean Manufacturing Strategy Based on Value Stream Mapping to Increase Production Process Efficiency in the Manufacturing Industry - Edi Sumarya; Muhammad Alwi; Ade Suhara; Rinto Yusriski (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2026)
remain competitive in a globalized market. Lean Manufacturing, particularly through the implementation of Value Stream Mapping (VSM) has been shown to be a highly effective strategy for improving production procedures through reducing waste, improving quality, and enhancing overall efficiency. This research uses a qualitative approach method via a review of existing literature to examine how Lean Manufacturing and VSM can improve production efficiency in manufacturing industries. The novelty of this study lies in systematically synthesizing empirical evidence on the combined application of Lean and VSM, highlighting not only operational improvements but also long-term sustainability and employee engagement, which have been less emphasized in prior studies. The findings indicate that Lean practices, when coupled with VSM, lead to significant reductions in lead times, waste, and inventory levels, while improving product quality and employee engagement. Key improvements observed include an 80% reduction in lead times, 75% reduction in waste, and 85% improvement in inventory management. The study also highlights challenges encountered during Lean implementation, such as resistance to change and the requirement for extensive training. Overall, the research demonstrates that Lean Manufacturing, supported by VSM, significantly enhances production efficiency, provides long-term operational benefits, and offers practical insights for organizations aiming to optimize manufacturing processes. Future studies should focus on integrating Lean with emerging digital technologies and exploring its application in complex manufacturing systems to further optimize workflows and sustain competitive advantage.